(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study determined the effect of flipped classroom technique on students’ academic achievement in financial accounting in Anambra State. Two research questions were raised and three null hypotheses were tested at 0.05 level of significance. The study adopted quasi-experimental non- equivalent control group design. The population of this study comprise 1,876 SS II financial accounting students from six education zones in the 257 public secondary schools in Anambra State. The sample of the study comprised 59 (38 males and 21 females) SS II financial accounting students in four intact classes selected using multi-stage sampling procedure. Financial AccountingAchievement Test (FAAT) was validated and used as instrument for data collection. The reliabilityof FAAT was determined using Kudder-Richardson Formula 20 (KR-20) which yielded a reliabilitycoefficient of 0.90. Mean and standard deviation were used to answer the research questions, whileAnalysis of Covariance (ANCOVA) was used to test the null hypotheses. Findings of the studyrevealed that flipped classroom technique has a higher effect on students’ academic achievement scores in financial accounting than the lecture method and the difference was significant. Theinteraction effect between flipped classroom technique and lecture method and gender on students’ academic achievement was not statistically significant. It was concluded that flipped classroomtechnique is not only gender-friendly but also an active instructional approach that positively enhancethe academic achievement of students in financial accounting. It was recommended among others that financial accounting teachers should utilize flipped classroom technique in their instructional deliverymore frequently than the lecture method